"Geeks and Geezers: how Era, values, and defining moments shape leaders" - Bennis, Warren G; Thomas, Robert J (Boston, 2002)
Today's young leaders grew up in the glow of television and computers; the leaders of their grandparents' generation in the shadow of the Depression and World War II. In a groundbreaking study of these two disparate groups affectionately labeled "geeks" and "geezers", legendary leadership expert Warren Bennis and leadership consultant Robert Thomas set out to find out how era and values shape those who lead. What they discovered was something far more profound: the powerful process through which leaders of any era emerge. "Geeks and Geezers" is a book that will forever change how we view not just leadership but the very way we learn and ultimately live our lives. It presents for the first time a compelling new model that predicts who is likely to become and remain a leader, and why. At the heart of this model are what the authors call "crucibles" utterly transforming periods of testing from which one can emerge either hopelessly broken, or powerfully emboldened to learn and to lead. Whether losing an election or burying a child, learning from a mentor or mastering a martial art, crucibles are turning points: defining events that force us to decide who we are and what we are capable of.
Keywords: Leadership